2006
DOI: 10.1038/sj.emboj.7600937
|View full text |Cite
|
Sign up to set email alerts
|

Processive movement of single kinesins on crowded microtubules visualized using quantum dots

Abstract: Kinesin-1 is a processive molecular motor transporting cargo along microtubules. Inside cells, several motors and microtubule-associated proteins compete for binding to microtubules. Therefore, the question arises how processive movement of kinesin-1 is affected by crowding on the microtubule. Here we use total internal reflection fluorescence microscopy to image in vitro the runs of single quantum dot-labelled kinesins on crowded microtubules under steady-state conditions and to measure the degree of crowding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
150
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 52 publications
28
150
1
Order By: Relevance
“…For this purpose, we used a CENP-E dimer-to-quantum-dot ratio of 1:4 in our assays (21,22). At this ratio, we observed that quantum dots traveled long distances [supporting information (SI) Movie S1], implying that individual CENP-E dimers can move processively along microtubules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we used a CENP-E dimer-to-quantum-dot ratio of 1:4 in our assays (21,22). At this ratio, we observed that quantum dots traveled long distances [supporting information (SI) Movie S1], implying that individual CENP-E dimers can move processively along microtubules.…”
Section: Resultsmentioning
confidence: 99%
“…We labeled our dimeric CENP-E construct with quantum dots (20,21) to visualize individual motor molecules through their movement on microtubules. Streptavidin-conjugated quantum dots were initially functionalized with biotinylated anti-histidine antibody and were then coupled to CENP-E dimers through the hexahistidine tag on their tail region.…”
Section: Resultsmentioning
confidence: 99%
“…In some experiments, it has been shown that kinesins stay tightly bound to the MT and wait when being blocked by an obstacle [337]. Although the general direction of kinesin motion is along individual protofilaments [301,41], recent experiments seem to show that occasional side steps onto neighboring protofilaments of the same MT are possible.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…The length of the displacement performed along the MT by a molecular motor between two phases of diffusion in the cytosol is called its run length. Typical run lengths for kinesin are of the order of one hundred steps [337] which in combination with the step size of 8 nm gives runs of about 1 µm in length. Kinesin is thus a processive motor.…”
Section: Kinesinmentioning
confidence: 99%
“…First, blockages or alteration of the microtubule surface (via MAPs) or post-translational modifications could alter the motor velocity. Indeed, when blockages are present on a MT, it can alter how fast other motors move, and MT acetylation can alter velocity as well [27,28]. Second, there could be alteration of a motor's enzymatic cycle via phosphorylation, or accessory proteins.…”
Section: The Significance Of Changes In In Vivo Cargo Velocitymentioning
confidence: 99%